EKSISTENSI PAJAK DAERAH SEBAGAI WUJUD PELAKSANAAN OTONOMI DAERAH DALAM KERANGKA GOOD FINANCIAL GOVERNANCE - Galih Arya Prathama (Media Iuris, 2018)
The increase of regional capacity in managing the needs of Regional Development accompanied by the Delegation of Authority from Central Government to Regional Government, has implications in increasing the need for Development Funds, while the Regions can’t continue to rely on the fulfillment of these needs to the Central Government. In response to this, in implementing Autonomy, the Regions are given additional Authority of Financial Management. Such authority, creates demands for the Regions to be creative and focused in achieving the Government Goals that have been established.,As an effort to execute duties and functions of Regional Government in the form of Regional Financial Management, then a region must be able to recognize the potential and explore all the resources it has. Local Government is expected to dig deeper related to the potential derived from its own financial resources, especially in order to meet the needs of government financing and development in the region, one of them through Local Own Revenue as one of the main sources of Regional Financial Reception. Independence of Local Own Revenue for a Regional Government, giving positive support to the ability of the region in meeting the needs to build the region. Thus, the greater source of income derived from the potential owned by a region, the more freely the area can accommodate the needs of community without the interest of Central Government which is not in accordance with the needs of people in the region.